2022 AICCRA Partnership Survey Results Report - Schuetz, Tonya; Ramírez, Margarita M.; Marchi, Julian; Bonilla-Findji, Osana; Poulos, Allison; Cali, Davide; Ageyo, Collins; Giombini, Valentina (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is a USD 60 million three-year project, funded by the World Bank and being led by CIAT, with participating partners from six countries: Ethiopia, Kenya, Zambia, Ghana, Mali and Senegal. This report provides an overview of the Satisfaction Survey that was disseminated to partners to gather their feedback on three of the intermediate Project Indicators (IPI), as laid out in the Project Implementation Arrangements. These indicators capture progress on (1 - IPI 1.3) the satisfaction with the usefulness, accessibility and relevance, particularly for gender and youth responsiveness, (2 - IPI 2.4) effectiveness of partnerships and (3 - IPI 3.3) the use or adaptation of AICCRA-funded climate-relevant knowledge products, decision-making tools and services.